(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article deals with the issues related to the use of linguistic tasks in the practice of teaching Russian language as an effective means for mastering the linguistic material. They contribute to the development of logical thinking, linguistic analysis and creative abilities of pupils. The definition of the concept “linguistic task” is presented, linguistic and linguodidactic classification is given, the methodology of using linguistic tasks at different stages of the Russian language lesson in high schools of Uzbekistan with Uzbek language of instruction is outlined, the role of linguistic tasks in the development of logical thinking, linguistic analysis skills and creative abilities of pupils is noted.